PENGARUH BAURAN PEMASARAN TERHADAP MINAT BELI KONSUMEN PADA RESTO MASAKAN KHAS ARAB MATH’AM ABU NAWAS KABUPATEN HULU SUNGAI UTARA - Hasanah, Nurul; Maulydia, Hajjah (Inovatif Jurnal Administrasi Niaga, 2021)
This study aims to obtain an actual:(1)picture of the influence of the marketing mix on consumer buying interest in the Arabic cuisine restaurant Math'am Abu Nawas, Hulu Sungai Utara Regency. The method used in this study is a descriptive method with a quantitative approach, while the data collection techniques used through an open questionnaire with 5 rating scales (Likert). In connection with the unknown number of population members, the determination of the sample size, according to Sugiono, 2014: 165, where multivariate analysis (correlation or multiple regression), for the sample size is 10 times the number of variables studied. Therefore the population used as a source of data in this study for the sample size used as much as 10 x 7 = 70 respondents The results of the calculations in this study are using SPSS version.25 by finding the results of the T test (partial) between the marketing mix variables using 4 sub-variables on the buying interest variable. buy, namely the Price Sub Variable (X.2) with the result 0.300 > 0.05, while the t-count value is 6,309 > t-table (1.995), while the results in the F (simultaneous) test in this study the F-count value is 8.393 while the f value -table of 2.50, it can be seen that the f-count value is 8.038 > f-table 2.50 with a significant level of 0.000 because the significant level is <0.05, then this regression model can be used for the dependent variable of Work Interest in other words it can be said that the independent variable Marketing Mix with The 4 Sub Variables together (simultaneously) have a significant effect on Buying Interest. Testing the coefficient of determination (R2) of 0.536, this result means that the independent variable Marketing Mix (X) using 4 Sub Variables explains 53.6% of the dependent variable, namely Purchase Interest (Y), it can be concluded that the Independent Variable Marketing Mix (X) has an effect on the Dependent Variable Buying Interest (Y) at the Math'Am Abu Nawas Resto, Hulu Sungai Utara Regency with a percentage of 53.6%, while 46.4% is influenced by variables not examined or included in the study.